Với các số dương a, b, c thỏa mãn a+b+c=3abc, chứng minh rằng:
\(a^4b^4+b^4c^4+c^4a^4>=3a^4b^4c^4\)
Với các số dương a, b, c. Chứng minh rằng:
\(\frac{a^5}{bc^2}+\frac{b^5}{ca^2}+\frac{c^5}{ab^2}>=a^2+b^2+c^2\)
Với các số dương a, b, c. Chứng minh rằng:
\(\frac{a^3}{\left(b+2c\right)^2}+\frac{b^3}{\left(c+2a\right)^2}+\frac{c^3}{\left(a+2b\right)^2}>=\frac{1}{9}\left(a+b+c\right)\)
\(\Sigma_{sym}a^4b^4\ge\frac{\left(\Sigma_{sym}a^2b^2\right)^2}{3}\ge\frac{\left(\Sigma_{sym}ab\right)^4}{27}\ge\frac{a^2b^2c^2\left(a+b+c\right)^2}{3}=3a^4b^4c^4\)
\(\Sigma\frac{a^5}{bc^2}\ge\frac{\left(a^3+b^3+c^3\right)^2}{abc\left(a+b+c\right)}\ge\frac{\left(a^2+b^2+c^2\right)^4}{abc\left(a+b+c\right)^3}\ge\frac{\left(a+b+c\right)^6\left(a^2+b^2+c^2\right)}{27abc\left(a+b+c\right)^3}\)
\(\ge\frac{\left(3\sqrt[3]{abc}\right)^3\left(a^2+b^2+c^2\right)}{27abc}=a^2+b^2+c^2\)